A Eu‐Doped Y‐Based Luminescent Metal–Organic Framework as a Highly Efficient Sensor for Nitroaromatic Explosives. Issue 8 (3rd February 2015) - Singha, Debal Kanti; Majee, Prakash; Mondal, Sudip Kumar; Mahata, Partha
Abstract: By an isomorphous substitution strategy, a three‐dimensional metal–organic framework (MOF), [Y1.8 Eu0.2 (PDA)3 (H2 O)1 ]· 2H2 O (1 ; PDA = 1, 4‐phenylenediacetate), has been synthesized by solvent‐assisted liquid grinding and direct heating. Dehydrated1 (1′ ) shows strong red photoluminescence through the antenna effect upon excitation at 240 nm. The red emissive property was used for the visual detection of nitroaromatic explosives in acetonitrile through luminescence quenching. Importantly, 1′ exhibited high sensitivity towards the sensing of 2, 4, 6‐trinitrophenol (TNP), 1, 3‐dinitrobenzene (DNB), 2, 4‐dinitrotoluene (DNT), 4‐nitrotoluene (NT), and nitrobenzene (NB) at very low concentrations (0 to 20 μM ). The estimated K SV (quenching constant based on linear Stern–Volmer plots) values are in the range 15.9 × 10 4 –1.1 × 10 4 M –1, which are amongst the highest values known for nitroaromatic‐sensing materials. For1′, sensing of TNP down to 23 ppb has been achieved. Abstract : The luminescence of a three‐dimensional metal–organic framework (MOF) with aromatic‐ligand‐sensitized Eu 3+ activators is useful for sensing trace amounts of nitroaromatic explosives in solution through the quenching phenomenon.